Targeting and Effectiveness of Social Safety Net Programmes: The Case of Zakat and BISP in Pakistan - Zoneira Summan Amjad; Usman Mustafa; Shujaat Farooq (NUST Journal of Social Sciences and Humanities)
Social Safety Nets are considered a window to improve lives of the poor. In Pakistan, various SSNs are functional, both in government and private sector. The present study made a comparison of Zakat and Benazir Income Support Programme (BISP) to evaluate the effectiveness, targeting and accuracy of both the programmes on a wide range of indicators including consumption, headcount poverty, and multidimensional poverty index. Data from the latest available 2013/14 round of Household Integrated Economic Survey (HIES) is used. The analysis reveals that both the Zakat and BISP recipients are under-reported as only 0.6 percent of the household reported as recipients of Zakat and 7 percent of the household reported that they got benefit from BISP programme. A comparison on socio-demographic profile of recipients of Zakat and BISP suggests that recipient households of both the Zakat and BISP are at a disadvantageous position as compared to the non-receiver households. However, BISP beneficiaries possess more assets, i.e., livestock, land and ownership of house. Zakat has quite limited coverage as compared to BISP. Same is the case with targeting